Children educational policy purchase decision among consumers in Lagos, Nigeria: awareness, trust and socio-economic status as influencing factors - Ajibola Abdulrahamon Ishola; Akeem Adekunle Kenku; Muhibat Ayoni Oladimeji-Araoye (Universitas Negeri Padang, 2022)
This study examines the influence of socio-economic status, trust in the insurance company, and knowledge/awareness of insurance products on the intention to purchase children's educational insurance policies. The research design for this study is a cross-sectional design. Three hundred participants were selected using a convience sampling technique. Data was collected via Standardised instruments and analysed using t-test for independent samples, Pearson correlation and multiple regression analysis at 0.05 level of significance (p<.05). The results demonstrated that Customers' socio-economic status, trust in the insurance company, attitude towards children's educational insurance policies, knowledge/awareness influenced and predicted intention to purchase children educational insurance policies. Given that knowledge, socio-economic status, trust and attitude are strongly linked to behaviour, marketers of insurance services targeting Nigerians must incorporating fundamental psychological reactions to these products into their marketing campaigns in order for people to embrace insurance products and their associated benefits.